Storage losses in net-wrapped, large, round bales of alfalfa hay - Taylor, R.K.; Kueck, D.L.; Addison, C.E.; Blasi, Dale A.; Maxwell, Thomas Mark; Shroyer, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Net- and twine-wrapped alfalfa hay bales were stored from July, 1990 to April, 1991 in three Kansas counties (Reno, Saline, and Stafford). Dry matter losses and changes in acid detergent fiber and acid detergent insoluble nitrogen levels during storage were not significantly different between net- and twine-wrapped bales. Although a significant difference in dry matter recovery between inside and outside bale storage occurred in Saline County, it was not considered important because all recoveries were high. No significant differences in ADF or ADIN increases were found between initial core samples and samples from the outer 4 in. of the bales at the end of storage. The minimal deterioration and weathering were probably due to below average rainfall (less than 14 in.) during the 9- mon. storage period. Net wrapping is probably not justified on the basis of reducing storage losses in low rainfall areas.
Keywords: Beef; Alfalfa; Hay; Round bales; Storage